Nexus between Financial Performance and Stock Prices during the COVID-19: Evidence from Indonesian Islamic Banks - Naili Rahmawati; Rusman Azizoma; Muhammad Muhajir Aminy; Bintang Pratiwi; Mohamed Saleem Ahamed Riyad Rooly (Journal of Enterprise and Development (JED), 2025)
Purpose: This study analyzes the impact of Return on Assets (ROA), Return on Equity (ROE), and Earnings Per Share (EPS) on the stock prices of Islamic banking companies listed on the Indonesian Stock Exchange during the COVID-19 pandemic (2020–2021), aiming to understand how key financial metrics influence stock valuations during economic uncertainty.Method: Using a quantitative approach, panel data regression analysis was conducted on a purposively selected sample of Islamic banking companies. The study assessed both individual and joint effects of ROA, ROE, and EPS on stock prices.Result: The results reveal that ROA, ROE, and EPS significantly affect stock prices, both individually and collectively. This indicates that profitability and earnings performance remain critical to market valuation even during crisis periods.Practical Implications for Economic Growth and Development: Findings offer practical value for investors and analysts using financial ratios to guide investment decisions. Bank managers can enhance shareholder value by improving these indicators, while policymakers may use the results to support the resilience of Islamic banking during economic disruptions.Originality/Value: This study contributes to the limited research on Islamic banking performance in crisis contexts by highlighting the continued relevance of fundamental financial indicators in influencing stock prices during the COVID-19 pandemic in an emerging market setting.